The impact of the digital economy on energy rebound: A booster or inhibitor? - Maliyamu Abudureheman (Economies, 2025)
Given the compromising effect of energy rebound on energy conservation efforts and environmental sustainability, plentiful research has focused on evaluating its size and scope in the past; however, there is a scarcity in the exploration of its potential drivers, especially the impacts of the digital economy. With the accelerating pace of worldwide digitalization, how the digital economy affects the energy rebound effect deserves special attention. We explored the underlying impacts of the digital economy on energy rebound and its influencing mechanisms for the first time in this study based on a panel dataset from China. Results show that most of the regions in China exhibited a partial rebound effect over the period 2007-2022, with an average value of 77.14%. Digital economy development exhibits a threshold effect on energy rebound with regard to energy efficiency improvement. That is, when the energy efficiency is low, digital economy development positively impacts the energy rebound, however, as the energy efficiency increases and surpasses a certain critical threshold, the digital economy can help mitigate the energy rebound effect. Energy prices and environmental regulation present a significant negative impact on energy rebound. Finally, several policy implications are highlighted based on the main findings of this study.
Keywords: 330; digital economy; energy efficiency; energy rebound effect